1998
DOI: 10.1038/28101
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the Stat3β homodimer bound to DNA

Abstract: STAT proteins are a family of eukaryotic transcription factors that mediate the response to a large number of cytokines and growth factors. Upon activation by cell-surface receptors or their associated kinases, STAT proteins dimerize, translocate to the nucleus and bind to specific promoter sequences on their target genes. Here we report the first crystal structure of a STAT protein bound to its DNA recognition site at 2.25 A resolution. The structure provides insight into the various steps by which STAT prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
774
1
8

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 770 publications
(811 citation statements)
references
References 43 publications
28
774
1
8
Order By: Relevance
“…7B). The search strategy also indicated that the helical pattern of UXT was homologous to the last three helices of the 4-helix bundle of transcription factor STAT (signal transducers and activators of transcription) 3b (P42227, residues 136-321) [32] (Fig. 7C).…”
Section: Uxt (Xp_033860)-mentioning
confidence: 95%
“…7B). The search strategy also indicated that the helical pattern of UXT was homologous to the last three helices of the 4-helix bundle of transcription factor STAT (signal transducers and activators of transcription) 3b (P42227, residues 136-321) [32] (Fig. 7C).…”
Section: Uxt (Xp_033860)-mentioning
confidence: 95%
“…These results strongly suggest that Stat3 activation is required for IL-6-induced di erentiation in the M1 macrophage model. Interest- Chen et al, 1998;Becker et al, 1998), the overall organization of Stats consists of an N-terminal domain (N) involved in cooperative binding to DNA, a four-helix bundle (4HB), a b-barrel (bBBL) which forms loops involved in DNA binding, the SH2 domain (SH2) and conserved tyrosine phosphorylation site (Y P ) which are essential for dimerization, and a C-terminal region involved in transactivation of transcription (AD). Three types of dominant-negative mutants are illustrated.…”
Section: Dominant-negative Mutants Implicate Stat3 In Myeloid Differementioning
confidence: 99%
“…Stat3 contains several functional domains including the Nterminal domain (ND), coiled-coil domain with four ␣-helices (CC), DNA binding domain (DB), linker domain (LK), SH2 domain, and C-terminal domain (CT) (Becker et al, 1998). To define the domain that binds to Isl1, we generated a series of FLAG-tagged truncation mutants of Stat3 that encode individual domains or their combinations as illustrated in Figure 5A.…”
Section: Mapping the Binding Domains Mediating Interaction Between Ismentioning
confidence: 99%